Determination Of Acute Poisoning Properties Of Vitis L. Plant Condensed Water-Syrup (Molasses) - Azimova A.Q; Makhmudov L.U; Islamov A.Kh (Genius Publishing Group, 2024)
This article presents information on medicinal properties, chemical activity, and results of pharmacological examination of water-syrup with condensed grape juice.
Keywords: Vitis L; brand; grape; pharmacology